Supporting International Students: Enhancing College Counselors' Multicultural Counseling Competence. Issue 2 (6th July 2019) - Kim, Nayoung; Oh, Seungbin; Mumbauer, Jayna
Abstract : International students experience significant difficulties as they adjust to the dominant culture in the United States. However, there is a substantial gap between the reported academic and sociological distress these students experience and their help‐seeking behaviors. This article reviews international students' distinctive challenges in seeking professional help and proposes guidelines to effectively support these students by enhancing college counselors' multicultural counseling competence.